A case of small lymphocytic lymphoma with hypersensitive reactions to mosquito bites as the first skin manifestation - Xue HAN; Yue LIN; Daping ZHONG; Guofu YAN; Wei HE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
We report a case of small lymphocytic lymphoma with hypersensitive reactions to mosquito bites as the first skin manifestation. A 49-year-old male presented with a 5-year history of repeated swollen and itching on the head and neck region after mosquito bites. The current episode occurred a week ago. The findings of dermatological examination included swollen erythemas covered with millet- to green bean-sized papules and vesicles accompanied with exudation on the right lateral cheek, the right part of posterior neck and right subscapular region. There were lymphadenopathies behind the right ear, in the lower right jaw, the bilateral neck and armpits, with tenderness. The histopathology of right cervical lymph node showed destruction of lymph nodes and a large number of small lymphocytes, with uniform morphology, less cytoplasm, inconspicuous nucleoli, and few mitotic figures. Immunohistochemistry showed CD20(+),Pax-5(+), CD3(-), CD5(+), CD23(+), Bcl-2(+), Bcl-6(-),CD10(-),Cyclin-D1(-),SOX-11(-),Mum-1(-),CD4(-),CD8(-),CD56(-),Ki-67(30%+). In situ hybridization showed EBER negative. Anti-EBV antibody (EB-VCA-IgG) levels were >750.0 U/mL. The diagnoses of chronic lymphocytic leukemia/small lymphocytic lymphoma and hypersensitivity to mosquito bites were made. The patient was transferred to the hematology department and is currently under follow-up because of no indication for treatment.